Oligo-Miocene variability in carbonate producers and platforms of the Coral Triangle biodiversity hotspot: habitat mosaics and marine biodiversity - Wilson, Moyra (Society for Sedimentary Geology, 2015)
A holistic approach is adopted here to evaluate basin-wide trends in carbonate systems, their subenvironments and the potential marine biodiversity partitioning between different habitats within the Coral Triangle biodiversity hotspot in central Southeast Asia. The Central Indonesian Kutai Basin is typical of many Cenozoic Southeast Asian basins in having extensive and varied carbonate systems, and is one of the few regions in the Coral Triangle with detailed systematic multitaxon evaluation of Oligo-Miocene deposits. The Kutai Basin may therefore provide data, when compared with other modern and global datasets, to better understand marine biodiversity development within the global diversity foci. Carbonate systems in the Kutai Basin included small-scale ephemeral features, such as delta-associated patch reefs, mixed carbonate-clastic shelves, and large-scale (> 10 km) land-attached and isolated carbonate platforms affected by varied energy regimes. Twenty-five–plus subenvironments or habitats are spread across the different carbonate systems, with the large-scale platforms hosting over 12–15 different habitats. These subenvironments include clastic-influenced mesophotic coral reefs/carpets, nonclastic- and clastic-influenced sea-grass beds, downslope reworked coral rubble, and shallow low-energy inner platform areas, to name a few. Perhaps paradoxically, the systems that two decades ago were almost unstudied, the clastic-influenced coral reefs/carpets, are now the only ones in the region to have been systematically studied for their marine biota. Detailed biotic studies have therefore only investigated < 4 of the 25-plus potentially habitable carbonate subenvironments within the basin.This variability of carbonate systems and their subenvironments, but paucity of detailed biotic data is typical of many basins within equatorial Southeast Asia. It is recognized that detailed multitaxon biotic studies are in their infancy for Southeast Asia, and that there are challenges of taxonomic bias and/or preservation for many groups within the fossil record. Currently, however, we cannot evaluate marine biodiversity partitioning across the varied habitat mosaics of Southeast Asian carbonate systems with possible pathways discussed for furthering this field of research. It is likely that we are (?grossly) underestimating biodiversity on a basin-wide and probably a system-wide scale. It is hoped that studies of this type will contribute towards better understanding of equatorial marine carbonate systems, their biological inhabitants and producers, and the spatio-temporal development of global biodiversity hotspots.